2022
DOI: 10.3389/fped.2022.904616
|View full text |Cite
|
Sign up to set email alerts
|

Chilblains-Like Lesions in Pediatric Patients: A Review of Their Epidemiology, Etiology, Outcomes, and Treatment

Abstract: Vascular pathologies associated with SARS-CoV-2 infection are poorly understood. Color and sensory changes to the extremities, often referred to as “COVID toes” or chilblains-like lesions, have been widely reported in children and adolescents since the onset of the pandemic, raising the concern that they could be a vasculitis secondary to the infection. However, it is unclear if the lesions are a result of the infection or an epiphenomenon. Most literature focuses on adults, and while there are reports on chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Chilblains were more frequent in children during the pandemic compared to the pre‐pandemic era ( 20 , 21 , 22 ). In a recent literature review, it was reported that 1,059 children developed chilblain‐like lesions that were likely associated with COVID‐19 ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chilblains were more frequent in children during the pandemic compared to the pre‐pandemic era ( 20 , 21 , 22 ). In a recent literature review, it was reported that 1,059 children developed chilblain‐like lesions that were likely associated with COVID‐19 ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chilblains were more frequent in children during the pandemic compared to the pre‐pandemic era ( 20 , 21 , 22 ). In a recent literature review, it was reported that 1,059 children developed chilblain‐like lesions that were likely associated with COVID‐19 ( 21 ). The more frequent occurrence of these lesions during late childhood to early adolescence and a male predominance were the striking common features in these reports ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…systemic lupus erythematosus) or immunological (e.g. Aicardi‐Goutières) condition 1 . Although this patient had a positive anti‐nuclear antibody, the titre was low positive and he was otherwise well.…”
Section: Answermentioning
confidence: 85%
“…Aicardi-Goutières) condition. 1 Although this patient had a positive anti-nuclear antibody, the titre was low positive and he was otherwise well. An underlying rheumatological condition was considered unlikely.…”
mentioning
confidence: 78%